Vaccine hesitancy and receipt of mandatory and optional pediatric vaccines in Shanghai, China - Mengdi Ji; Zhuoying Huang; Jia Ren; Abram L. Wagner (Human Vaccines & Immunotherapeutics, 2022)
Given increased global concern about vaccine hesitancy, this study estimates coverage of mandatory vs non-mandatory vaccines in children, and assesses whether vaccine hesitancy among young parents relates to their childʻs eventual vaccination status in Shanghai, China. In a cohort study within Shanghai, China, we ascertained vaccine hesitancy among parents of young infants, and later abstracted their childʻs electronic immunization records. We measure full coverage of vaccines on the mandatory, and publicly funded Expanded Program on Immunization (EPI). Non-EPI vaccines included pneumococcal conjugate vaccine, Haemophilus influenzae type b vaccine, and rotavirus vaccine. Vaccine hesitancy was linked to vaccine uptake through mixed effects logistic regression models. Among 972 children, full coverage of all EPI vaccines by 15 months was 95%, compared to dose 1 coverage of pneumococcal conjugate vaccine at 13%, Haemophilus influenzae type b vaccine at 68%, and rotavirus vaccine at 52%. Vaccine hesitancy was not significantly linked with full coverage of all EPI vaccines (OR: 1.55, 95% CI: .89, 2.72), but coverage in the vaccine hesitant was lower for pneumococcal conjugate vaccine dose 1 (OR: .70, 95% CI: .53, .91), and rotavirus vaccine dose 1 (OR: .69, 95% CI: .56, .86). Disparities by education level were not significant for EPI vaccines, but were for dose 1 of pneumococcal conjugate vaccine rotavirus vaccine. Overall, vaccine hesitancy was related to lower uptake of non-EPI, but not EPI vaccines. Shanghai has a robust system for insurance equitable access to EPI vaccines, but if vaccine hesitancy grows, it could reduce coverage of non-EPI vaccines.